2016
DOI: 10.1126/sciadv.1501671
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature plasticity of olivine revisited with in situ TEM nanomechanical testing

Abstract: The flow properties of the mineral olivine under lithospheric conditions, as seen in the transmission electron microscope (TEM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(101 citation statements)
references
References 36 publications
5
96
0
Order By: Relevance
“…This difference implies the operation of an additional deformation mechanism, which was probably low‐temperature plasticity. Therefore, in Figure , we compare the experimental data to the commonly used flow law of Evans and Goezte () for low‐temperature plasticity, and the recently published flow law of Idrissi et al (). The flow laws for low‐temperature plasticity are in better agreement with the experimental data for the [011] c sample than is the flow law of Bai et al (), indicating a large contribution of low‐temperature plasticity to the strain rate.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This difference implies the operation of an additional deformation mechanism, which was probably low‐temperature plasticity. Therefore, in Figure , we compare the experimental data to the commonly used flow law of Evans and Goezte () for low‐temperature plasticity, and the recently published flow law of Idrissi et al (). The flow laws for low‐temperature plasticity are in better agreement with the experimental data for the [011] c sample than is the flow law of Bai et al (), indicating a large contribution of low‐temperature plasticity to the strain rate.…”
Section: Discussionsupporting
confidence: 79%
“…Mechanical data from load stepping tests on samples deformed in the [011] c and [110] c orientations at 1000°C and 1200°C, respectively. The lines indicate strain rates predicted by previously published flow laws for dislocation creep (Bai et al, ) and low‐temperature plasticity (Evans & Goezte, ; Idrissi et al, ).…”
Section: Resultsmentioning
confidence: 94%
“…We conclude that the sample CMT17-2 deformed in the brittle field by micro fracturing for a strain > 3% (at 1127 MPa, where the cuve flattens abruptly), while the other samples underwent no brittle failure. Rigid body grain rotation cannot be observed, since the , Chopra & Paterson (1984), Hirth & Kohlstedt (2003), Raterron et al (2004), Keefner et al (2011, Demouchy et al (2013), Boioli et al (2015), Idrissi et al (2016), Tielke et al (2016, shear on (100)[001] for 1000 °C and (001)[100] for 1200 °C) and Tielke et al (2017, dry/wet glide for 1000 °C and wet climb for 1200 °C, 11-16 ppm H2O wt. or 190-260 ppm H/10 6 Si).…”
Section: Deformation Mechanisms and Microstructurementioning
confidence: 99%
“…Experiments performed at temperatures relevant to the uppermost lithospheric mantle (≤ 1000 °C, e.g. Raterron et al, 2004;Demouchy et al 2009Demouchy et al , 2013Demouchy et al , 2014Mei et al, 2010;Idrissi et al, 2016;Tielke et al, 2016) report a lower strength of olivine than was expected from extrapolation of high-temperature flow laws. The low temperature plasticity is a key to understanding deformation of the shallow upper mantle (Hirth & Kohlstedt, 1995) but also in subducting slabs Kirby, 1980;, where it governs the stress storage capacity and therefore the maximal stress release of deep earthquakes (e.g., Proietti, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have reported Peierls stresses for olivine, ranging widely from as little as 3.8 GPa (Idrissi et al 2016) to ~15 GPa (Demouchy et al 2013), although typical values are in the range 5-10…”
Section: Introductionmentioning
confidence: 99%